Impact of Biological Sex on Complications, Lengths of Stay, Readmission Rates, and Costs of Care Following Primary Total Knee Arthroplasty - Swiggett, Samuel J.; Mannino, Angelo; Vakharia, Rushabh M.; Ehiorobo, Joseph O.; Roche, Martin W.; Mont, Michael A.; Erez, Orry (The Journal of Knee Surgery, 2021)
The impact of gender on total knee arthroplasty (TKA) postoperative complications, readmission rates, and costs of care has not been often evaluated. Therefore, the purpose of this study was to investigate which sex had higher rates of: (1) medical complications; (2) implant complications; (3) lengths of stay (LOSs); (4) readmission rates; and (5) costs after TKA. A query was performed using an administrative claims database from January 1, 2005, to March 31, 2015. Patients who had TKAs were identified using International Classification of Diseases, Ninth Revision and Current Procedural Terminology codes. Males and females were filtered separately and matched according to age and various medical comorbidities leading to 1,590,626 patients equally distributed. Primary outcomes analyzed included 90-day medical complications, LOSs, 90-day readmission rates, in addition to day of surgery and total global 90-day episode of care costs. Pearson's chi-square analyses were used to compare medical complications and readmission rates. Welch's t-tests were used to test for significance in matching outcomes and costs. A p-value of less than 0.01 was considered statistically significant. Males had a smaller risk of complications than women (1.35 vs. 1.40%, p < 0.006) and higher rates of implant-related complications (2.28 vs. 1.99%, p < 0.0001). Mean LOSs were lower for males: 3.16 versus 3.34 days (p < 0.0001). The 90-day readmission rates were higher in men (9.67 vs. 8.12%, p < 0.0001). This study demonstrated that males undergoing primary TKA have lower medical complications and shorter LOSs then their female counterparts. However, males have higher implant-related complications, readmission rates, and costs of care.
Keywords: total knee arthroplasty; gender; complications; readmission; Medicare